2022
DOI: 10.21203/rs.3.rs-1975854/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatotoxicity and Nephrotoxicity induced by fipronil and lead acetate and their mixture as well as evaluation of therapeutic effects of camel milk against their harmful.

Abstract: Elevated environmental pollution of lead and fipronil blamed for chronic toxicity. Fipronil and lead acetate are commonly used but now no adequate data available concerning side harmful of their mixture. The present work studied the curative effects of camel milk against lead and fipronil toxicity individually and their mixture. The lead acetate or fipronil and their mixture significantly induction deteriorated kidneys and liver function parameters as well as lipid profile and oxidative stress in the both orga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…In lead acetate-poisoned rats, camel milk restored hepatic enzyme function (Hailu et al 2016;Ahamad et al 2017;Abrhaley and Leta 2018). Camel milk protects male albino rats from lead acetate and fipronil's hepatotoxic and nephrotoxic effects (Abdel-Mobdy et al 2023). Al-Asmari et al (2017) observed that camel milk reduced oxidative stress and inflammation to protect and regenerate hepatocyte membranes.…”
Section: Camel Milk Against Heavy Metal Toxicitymentioning
confidence: 99%
“…In lead acetate-poisoned rats, camel milk restored hepatic enzyme function (Hailu et al 2016;Ahamad et al 2017;Abrhaley and Leta 2018). Camel milk protects male albino rats from lead acetate and fipronil's hepatotoxic and nephrotoxic effects (Abdel-Mobdy et al 2023). Al-Asmari et al (2017) observed that camel milk reduced oxidative stress and inflammation to protect and regenerate hepatocyte membranes.…”
Section: Camel Milk Against Heavy Metal Toxicitymentioning
confidence: 99%